Activity trackers and fitness centre members : motivation and awareness - Kettunen, Eeva (2017)
Worldwide, physical activity level of the general population is below what is recommended for achieving a healthy lifestyle. At the same time the use of fitness related products, such as fitness applications for smartphones and wearable activity monitors are increasing, particularly in fitness centre settings. This trend leads to questions about what is the influence of the activity trackers on a person’s motivation to exercise, and whether these devices can contribute to improving the health of the general population.